2005
DOI: 10.1002/ejic.200400657
|View full text |Cite
|
Sign up to set email alerts
|

Aerogel and Xerogel Catalysts Based on θ‐Alumina Doped with Silicon for High Temperature Reactions

Abstract: Numerous materials (supports and catalysts) based on alumina have been prepared using the sol-gel process and carbon dioxide supercritical drying. In this work two types of solids, i.e. xerogels and aerogels, were systematically compared and a way of introducing platinum metal with a content of 5% percent by weight was examined. The structural data, the surface area, Pt dispersion and catalytic activity for the decomposition of the propellant were measured for the various samples. The (Al 2 O 3 ) 0.88 (SiO 2 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Balakrishnan and Gonzalez prepared aerogel and xerogel catalysts of platinum-alumina systems, and concluded that the aerogels were inferior in comparison to the corresponding xerogels as far as the surface area and metallic dispersion were concerned [7]. The comparison of aerogel and xerogel catalysts were also done by Courtheoux et al [8] and Popa et al [9]; for the catalytic propellant decomposition the aerogels showed lower activities, although they had superior properties compared with xerogels. Sault et al developed a platinum-alumina aerogel catalyst via a combination of inverse micelle technology with sol-gel processing [10]; although the aerogel exhibited higher turnover frequency for propane dehydrogenation than the xerogel, the Pt diameter and the BET surface area were much larger and smaller, respectively, for the aerogels.…”
Section: Introductionmentioning
confidence: 95%
“…Balakrishnan and Gonzalez prepared aerogel and xerogel catalysts of platinum-alumina systems, and concluded that the aerogels were inferior in comparison to the corresponding xerogels as far as the surface area and metallic dispersion were concerned [7]. The comparison of aerogel and xerogel catalysts were also done by Courtheoux et al [8] and Popa et al [9]; for the catalytic propellant decomposition the aerogels showed lower activities, although they had superior properties compared with xerogels. Sault et al developed a platinum-alumina aerogel catalyst via a combination of inverse micelle technology with sol-gel processing [10]; although the aerogel exhibited higher turnover frequency for propane dehydrogenation than the xerogel, the Pt diameter and the BET surface area were much larger and smaller, respectively, for the aerogels.…”
Section: Introductionmentioning
confidence: 95%
“…The crystalline phases were identified by comparison with powder diffraction files (PDF) standards from ICDD (PDF number: TiO 2 anatase: 21-1272; TiO 2 rutile: 21-1276). The crystallite sizes were determined from the Scherrer equation (Popa et al 2005) using the integrated width corrected from apparatus using LaB 6 as a standard.…”
Section: Samples Characterizationmentioning
confidence: 99%
“…The effect of drying technique (subcritical drying xerogel; CO 2 supercritical drying aerogel) was studied when silicon was selected as a dopant to be inserted in γ -alumina. The introduction method of 5 wt.% Pt was also discussed [189]. The impact on thermal stability and 79 wt.% HAN-21 wt.% H 2 O decomposition catalytic activity of both drying procedures and active phase introduction (impregnation against one-step addition before sol formation) [188], xerogels and aerogels of alumina were compared.…”
Section: Catalytic Decomposition Of Han and And Hnfmentioning
confidence: 99%